The angel and the wild animal - Foreman, Michael, 1938- (London : Beaver, 1989)
Sometimes the house is inhabited by a bright and peaceful angel, sometimes by a wild and rampaging animal, but most of the time by a little boy.
"First published by Andersen Press Ltd., London"--T.p. verso.
2.3
K-3.
K-3
Keywords: Behavior -- Fiction; Human behavior -- Fiction